2010
DOI: 10.1016/j.ijid.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of susceptibility testing methods for polymyxin

Abstract: The E-test and agar dilution methods showed good concordance with BMD. The disk diffusion method can be useful for initial screening in diagnostic laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
62
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 12 publications
8
62
0
2
Order By: Relevance
“…For colistin resistant, E-test was further used after the initial screening using disk diffusion. Although low sensitivity of E-test on detecting colistin resistant strains has been reported recently, 58 our results in this study was considered reliable as no zone of inhibition was observed for three colistin strains in two repeated experiments. However, the strains will be further subjected to the other MIC detection methods, such as broth macrodilution (TDS) and broth microdilution with polysorbate 80 (BMD-T) for further comparison and evaluation.…”
supporting
confidence: 58%
“…For colistin resistant, E-test was further used after the initial screening using disk diffusion. Although low sensitivity of E-test on detecting colistin resistant strains has been reported recently, 58 our results in this study was considered reliable as no zone of inhibition was observed for three colistin strains in two repeated experiments. However, the strains will be further subjected to the other MIC detection methods, such as broth macrodilution (TDS) and broth microdilution with polysorbate 80 (BMD-T) for further comparison and evaluation.…”
supporting
confidence: 58%
“…Numerous studies have demonstrated a strong correlation between agar dilution and BMD (70,75,76), with the exception of results obtained with P. aeruginosa and S. maltophilia isolates from cystic fibrosis patients (77,78). One advantage of the agar dilution method is the ability to test multiple strains on the same plate and the possibility to semiautomate the method.…”
Section: Dilution Methodsmentioning
confidence: 99%
“…The MIC value is defined by the intersection of the lower part of the ellipse-shaped growth inhibition area with the test strip. When the intersection occurs around the MIC endpoint, the highest MIC intersection is recorded (75). When small colonies grow within the zone of inhibition, the strain must be considered heteroresistant to colistin, and the highest MIC intersection is recorded (75,81).…”
Section: Nonautomatic Systems (I) Dd Test (Kirby-bauer Procedure)mentioning
confidence: 99%
See 1 more Smart Citation
“…Manual BMD, however, is laborious and not performed in many routine clinical microbiology laboratories, which often rely on diffusion or automated systems for susceptibility testing. Moreover, and somewhat paradoxically in view of the drugs' poor diffusion in agar, diffusion methods (both disk and gradient strips) have been found to have unacceptably high levels of false susceptibility (or very major errors [VMEs]) in multiple studies (12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) (Table 1). Both the CLSI and EUCAST have now advised against diffusion methods for the polymyxins, removing disk diffusion interpretive criteria for them from their guidance documents (9,15,22).…”
mentioning
confidence: 99%